Droga Austrii do członkostwa w Unii Europejskiej - Szymczyński, Tomasz R. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
In the Author’s opinion the case of Austria demonstrates at least two highly significant issues in the context of obtaining membership of the EU. Firstly, even an economically highly developed country (GNP in excess of the average level of the EU member states) as well as a considerable degree of integration with the EU even prior to the accession (EEA member) did not suffice to prevent Austrian society from experiencing negative consequences immediately after the accession. This is strictly related to the other significant phenomenon. A considerable increase of negative approaches towards membership, emerging among Austrian society, to a significant degree resulted from the excessive expectations of the merits which were supposed to be shared by the society following the accession.